The theoretical basis of bisignal formation of information flow in computer systems with open optical signals - Grynchyshyn, Taras; Yakymenko, Ihor; Nykolajchuk, Yaroslav; Kasyanchuk, Mykhajlo (Видавництво Львівської політехніки, 2010)
The theoretical basis of bisignal formation of information flow in computer systems (CS) with open optical signal (OOS) was proclaimed. Analytic expressions of signals attenuation in computer systems OOS with compensated multiplicative noise were determined.
Keywords: open optical signal; bisignal formation of information flow